Two new species of Sabacon Simon, 1879 (Opiliones: Dyspnoi: Sabaconidae) from Yunnan Province, China - Zhao, Li Kun; Martens, Jochen; Zhang, Chao (Zootaxa, 2018)
Two new species of the harvestman genus Sabacon Simon, 1879 are recorded from Yunnan Province, southern China, Sabacon monacanthus sp. n. (male and female; relationships unclear) and S. suzukii sp. n. (male and female; closely related to S. kangding Martens, 2015 from Sichuan Province, southwestern China).